2017
DOI: 10.1080/10803548.2017.1373487
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic interventions for prevention of work-related musculoskeletal disorders in a small manufacturing assembly line

Abstract: This study involves performing improvements in workstation specification using a three-dimensional human modeling tool and proposing well-balanced work scheduling (WBWS) to prevent work-related musculoskeletal disorders (WMSDs) in a small manufacturing plant. To analyze risk factors of WMSDs, various tasks at 10 different types of workstation were evaluated with detailed motion analysis using a customized checklist. Questionnaires were administered to 27 workers to evaluate symptoms related to WMSDs. Revised w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
10
2
4
Order By: Relevance
“…By contrast there are studies with larger sampling, such as the study carried out in Germany with a sample of 11,790 people aged 17-90 years, but the type of occupational activity that people were allocated to was not categorized. This Germany study validated the strong association between body height and increased handgrip strength, with each 10 cm in height associated with an increase in handgrip strength of 2 to 4 kg [18]. In another study carried out in the British population, the sample was 1645 people but did not report the activities the participants performed.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…By contrast there are studies with larger sampling, such as the study carried out in Germany with a sample of 11,790 people aged 17-90 years, but the type of occupational activity that people were allocated to was not categorized. This Germany study validated the strong association between body height and increased handgrip strength, with each 10 cm in height associated with an increase in handgrip strength of 2 to 4 kg [18]. In another study carried out in the British population, the sample was 1645 people but did not report the activities the participants performed.…”
Section: Introductionsupporting
confidence: 56%
“…To ensure normative values for healthy workers, the following exclusion criteria were applied: a) minimum value of 10 kg of handgrip force (exclusion workers; b) presentation of any medical restriction or occupational disease from the industry's occupational department; c) SF-12 criteria (Short Form Health Survey) with a score lower than 5% of the physical component score of the quality of life scale [18].…”
Section: Samplementioning
confidence: 99%
“…That situation occurs because the interaction with the workload, working time, and the intensity of physical exposure can reduce the muscle's ability to generate energy, which in turn facilitates the development of these age-related syndromes (8,9). Some measures are used to diagnose sarcopenia and frailty syndrome, such as handgrip strength (HGS), which is considered a good inter-rater reliability (4,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…That situation occurs because the interaction with the workload, working time, and the intensity of physical exposure can reduce the muscle’s ability to generate energy, which in turn facilitates the development of these age-related syndromes (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that WMSDs is a second-high incidence of occupational diseases only next to occupational mental illness because of its huge economic loss every year. At present, a number of scholars have carried out a series of related studies on WMSDs [18][19][20][21][22][23]. Lukman et al indicated that drivers who performed MMH of heavy loads and adopted awkward postures are at a higher risk of developing WMSDs [19].…”
Section: Introductionmentioning
confidence: 99%